2012
DOI: 10.1007/s10616-012-9430-9
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on nonviral genetic modifications in cord blood and bone marrow mesenchymal stem cells

Abstract: The focus of both clinical and basic studies on stem cells is increasing due to their potentials in regenerative medicine and cell-based therapies. Recently stem cells have been genetically modified to enhance an existing character in or to bring a new property to them. However, accomplishment of declared goals requires detailed knowledge about their molecular characteristics which could be achieved by genetic modifications mostly through nonviral transfection strategies. Capable of differentiating into multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…That this view may be a little bit too simple has been brought to our attention by a thorough comparative study of the influence of three lipid-based transfection agents on hepatocytes focusing on various side effects on cellular metabolism presented in this issue of Archives of Toxicology (Böttger et al 2015). While this study confirmed the high efficiency of the tested transfection agents in silencing transcription of target genes by respective siRNAs together with a low cytotoxicity for the hepatocytes (Bakhshandeh et al 2012;Gao et al 2012), it demonstrated considerable effects on different aspects of lipid and amino acid metabolism of these cells (Böttger et al 2015). Using highly sophisticated shotgun lipidomics analysis, Böttger et al (2015) showed that all tested transfection agents altered the hepatocellular accumulation of triglycerides (two up and one down).…”
mentioning
confidence: 62%
“…That this view may be a little bit too simple has been brought to our attention by a thorough comparative study of the influence of three lipid-based transfection agents on hepatocytes focusing on various side effects on cellular metabolism presented in this issue of Archives of Toxicology (Böttger et al 2015). While this study confirmed the high efficiency of the tested transfection agents in silencing transcription of target genes by respective siRNAs together with a low cytotoxicity for the hepatocytes (Bakhshandeh et al 2012;Gao et al 2012), it demonstrated considerable effects on different aspects of lipid and amino acid metabolism of these cells (Böttger et al 2015). Using highly sophisticated shotgun lipidomics analysis, Böttger et al (2015) showed that all tested transfection agents altered the hepatocellular accumulation of triglycerides (two up and one down).…”
mentioning
confidence: 62%
“…However, use of GFP requires a gene transfer agent, such as a virus that is non-integrating or, preferably from a biosafety point of view, a non-viral vector. These, however, are limited by the requirement of large cell numbers, high levels of cell death and low transfection efficiency (Bakhshandeh et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, lack of an effective delivery system of miRNAs still remains a major problem. Viral and nonviral vectors have been developed as two common types of vectors for delivery of miRNAs to solve the mentioned problems (Bakhshandeh, Soleimani, Hafizi, & Ghaemi, 2012). Moreover, a recent study conducted by Tavanafar et al (2017) indicated that restoration of miR-143 expression by plasmid vector (pCMV-MIR-143) in breast adenocarcinoma cells reduced KRAS, Vimentin, CXCR4, and MMP9 and increased E-Cadherin expression.…”
Section: Conjugation With Small Transport Domainsmentioning
confidence: 99%